Contractile protein antigens in the cells of malignant melanoma of the choroid and their diagnostic significance. Issue 6 (June 1978) - Rahi, A. H.; Garner, A.; Malaty, A. H.
Abstract : Sera from patients with proved and suspected melanoma of the uvea and from patients with innocuous uveal naevi were found by immunohistological techniques to have an affinity for the cytoplasm of malignant choroidal melanoma cells in an appreciable proportion of cases. The responsible antibodies were subsequently shown to react with smooth muscle protein in a variety of tissues and not to be melanoma-specific. It was also shown by electron microscopy that microfilaments consistent with contractile protein are a feature of the cytoplasm of malignant choroidal melanoma cells. The latter observations, which do not appear to have been reported previously, mean that false positives are to be expected if immunodiagnostic techniques are used for the recognition of malignant disease of the uvea, especially as smooth muscle antibodies can occur in non-neoplastic ocular diseases.